Ductal Carcinoma in situ of the female Breast - Mohamed, Elgaili; Mohammadani, A.A.; Elkhatim, Mukhtar (Gezira Journal of Health Sciences, 2007)
The breast is the most common site of cancer in females in many parts of the world. Mammary carcinoma is either ductal arising from ducts or lobular arising from lobules. When ductal carcinoma is still confined to the mother duct it is called ductal carcinoma in situ "DCIS" & when confined to the lobules it is called lobular carcinoma in situ "LCIS".